Sosialisasi dan Edukasi Motode Pencegahan Covid-19 di Desa Sidoharjo I Pasar Miring - Revita Sari; Dea Nurul Ifada (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2022)
Covid-19 is a disease caused by infection with the Sars-CoV-2 virus, first identified in Wuhan City, in Hubei Province, China in December 2019, where the Covid-19 virus is a virus that can be transmitted. As a result of people's actions that lack awareness to comply with the regulations set by the government, many people are exposed to the Covid-19 virus which has become an epidemic. The aim of this author is to help the public by providing information about the dangers of Covid-19, helping the public to maintain their immune system by utilizing the properties of the red ginger plant as a health drink for the public during the pandemic. And provide Covid-19 education to kindergarten children so they know about the dangerous virus that is currently endemic. The author uses several methods, namely the first is the observation method, the second is the interview method. Based on data from observations carried out in Sidoharjo I Pasar Miring Village and carried out on community behavior in implementing health protocols in the first week and second week, it can be concluded that the community does not care about the dangers of the spread of the corona virus, so many people do not comply with the health protocols that have been implemented. determined by the government. This way of thinking in society is called cognitive bias, which always makes mistakes in thinking and interpreting things. To avoid cognitive bias, especially in the case of the Covid-19 outbreak, people should be more careful in making decisions and acting, they should be more careful in making decisions and acting, so that everything they do does not have a negative effect on other people, especially In terms of daily activities carried out both indoors and outdoors, health protocols must be adhered to.